Необхідність розвитку емпатії в іграх на заняттях у ЗВО. - Данилович, Оксана Дмитрівна (My University, 2026)
The study is dedicated to necessity of empathy development using games. Not enough attention is given to the development of empathy. This tendency has a negative influence on the personality, professional relations, everyday life. Cultivation of empathy will teach students to be kinder, more delicate, patient, so their relations in life and at work will be fruitful avoiding conflicts. Game method allows to develop empathy subtly. There may be games for acquiring empathy and also games combining professional skills.
Keywords: empathy, games, development